2021
DOI: 10.3390/genes12081178
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Elexacaftor/Tezacaftor/Ivacaftor Therapy in Three Subjects with the Cystic Fibrosis Genotype Phe508del/Unknown and Advanced Lung Disease

Abstract: We evaluated the effectiveness and safety of elexacaftor/tezacaftor/ivacaftor (ELX/TEZ/IVA) in three subjects carrying the Phe508del/unknown CFTR genotype. An ex vivo analysis on nasal epithelial cells (NEC) indicated a significant improvement of CFTR gating activity after the treatment. Three patients were enrolled in an ELX/TEZ/IVA managed-access program, including subjects with the highest percent predicted Forced Expiratory Volume in the 1st second (ppFEV1) < 40 in the preceding 3 months. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…In a retrospective study of severe CF patients on compassionate therapy with Trikafta, 6MWT increased by a mean of 42 m 36 . A pilot study in three patients found that treatment with Trikafta led to significant improvement in 6MWT 37 . These results could correlate to the significant improvement in breathing indices post Trikafta.…”
Section: Discussionmentioning
confidence: 92%
“…In a retrospective study of severe CF patients on compassionate therapy with Trikafta, 6MWT increased by a mean of 42 m 36 . A pilot study in three patients found that treatment with Trikafta led to significant improvement in 6MWT 37 . These results could correlate to the significant improvement in breathing indices post Trikafta.…”
Section: Discussionmentioning
confidence: 92%
“…Expanding usage of ETI to population not studied in the original clinical trials, use for PwCF and ADL, based primarily on a FEV1pp <40% or referral/evaluation for lung transplantation demonstrated improvements in FEV1pp [30][31][32][33][34] , BMI [31][32][33][34] , CFQ-R 32,34 , and decreases in antibiotic use/exacerbations 32,34 . Where reported, oxygen use was decreased/eliminated 32,34 , with one study demonstrating a decrease in noninvasive ventilation use 31 . Most importantly, transplantation status primarily changed in a positive direction, with decreases in transplant related discussions, referrals, and wait list numbers [30][31][32][33] .…”
Section: Elexacaftor/tezacaftor/ivacaftormentioning
confidence: 99%
“…Despite the development of therapeutic regimens, patient quality of life remains limited and even the most successful compounds do not achieve wild type (WT) level conductance [ 5 , 6 ]. The ∆F508 deletion mutation accounts for the majority of the CF population, making up approximately 70% of all patients, although its prevalence varies depending on the geographical origin of the patients [ 7 , 8 ]. ∆F508-CFTR is a class II mutation known for its trafficking defect caused by misfolding and ER retention and degradation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…∆F508-CFTR is a class II mutation known for its trafficking defect caused by misfolding and ER retention and degradation [ 8 ]. In 2015, ivacaftor-lumacaftor (Orkambi) was approved for use in patients aged 12 years or higher and homozygous for the ∆F508 mutation and was recently extended to include those aged 6–11 years old [ 7 , 9 ]. Orkambi is a combination treatment consisting of a small molecule corrector compound (VX-809, lumacaftor) that promotes protein stability and forward trafficking [ 10 ], and a small molecule potentiator (VX-770, ivacaftor) that promotes the open state of the channel [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation